DEVELOPMENT OF INTERNATIONAL TRADE IN THE CONTEXT OF INTERNATIONAL MANAGEMENT (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. Integration into the global economy and active participation in international trade contribute to economic development, job creation, and improved living standards. The application of international management in this context helps companies to effectively manage their international operations, adapt to different cultural and regulatory environments, and ensure sustainable development in the global economy.The purpose of the article. International trade is an important element of the global economic system that affects the development and welfare of countries. The main purpose of this article is to study the essence of international trade and its role in the system of international management. Formulation of the goal allowed us to identify a number of tasks to clarify the essence of international trade and the main factors of its development, to analyze the trends in Ukraine's trade with the European Union and the rest of the world.Metods. The study of international trade development in the context of international management requires the use of empirical research methods and analysis of statistical data that allow for a comprehensive analysis of market dynamics, the commodity structure of international trade, and the impact of global processes.Results. The article proves that international trade is a central link in the complex system of the global economy and plays a key role in the interaction between countries and regions of the world, influencing their economies, politics and society. It is also determined that international trade provides countries with access to a variety of goods and services that they do not produce or cannot produce on their own. The paper substantiates the importance of import and export growth in developed countries and identifies the interrelationships between different regions of the world. An important aspect of Ukraine's international trade based on Ukraine's relations with the European Union is also highlighted. The steps that Ukraine is taking to maintain such relations are also outlined. Based on the analysis, it is proved that Ukraine's exports are growing, especially in the context of trade with the EU, but there are certain dynamics and peculiarities in interaction with other regions of the world.Conclusiоns. The development of Ukraine's export potential and integration into the global economy are possible only if the structure of international trade is radically improved. To achieve these goals, it is necessary to use various forms of international economic cooperation.
Keywords: international trade, international trade relations, structure of international trade, international trade in the system of international management, trends in Ukraine's trade with the European Union.